Social media monitoring as a way to learn about consumer insights - Soltanifar, Mariusz (Henry Stewart Talks, 2019)
Brand24, Globalisation of Brand24, Social media monitoring, Brand trust, Building brand trust, Brand awareness, Converged media content strategy, Consumer relationship, How Brand24 met the challenge